STUDY OF THE PHYSICO-CHEMICAL PROPERTIES OF A LOW- TEMPERATURE HEAT CARRIER BASED ON POTASSIUM CARBONATE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The physicochemical properties of a low-temperature coolant based on potassium carbonate have been studied, which is associated with determining the composition and the possibility of adjusting coolants based on potassium carbonate with a freezing point.
Keywords: low-temperature coolant based on potassium carbonate, freezing point, density, viscosity, flow rate, flow inhibitors, carbon steel, aluminum alloy.